Accounting for Income Distribution Trends : A Density Function Decomposition Approach - Stephen P. Jenkins; Philippe van Kerm (Institute for the Study of Labor (IZA), 2004)
This paper develops methods for decomposing changes in the income distribution using subgroup decompositions of the income density function. Overall changes are related to changes in subgroup shares and changes in subgroup densities, where the latter are broken down further using elementary transformations of individual incomes. These density decompositions are analogous to the widely-used decompositions of inequality indices by population subgroup, except that they summarize multiple features of the income distribution (using graphs), rather than focusing on a specific feature such as dispersion, and are not dependent on the choice of a specific summary index. Nonetheless, since inequality and poverty indices can be expressed as PDF functionals, our density-based methods can also be used to provide numerical decompositions of these. An application of the methods reveals the multi-faceted nature of UK income distribution trends during the 1980s.
Keywords: C14; D31; D33; 330; income distribution; inequality; density functions; subgroup decompositions; Einkommensverteilung; Disparitätsmass; Dekompositionsverfahren; Schätzung; Theorie; Grossbritannien